Persepsi Masyarakat Terhadap Pelaksanaan Program Sanimas Di Kampung Yoboi Distrik Sentani Kabupaten Jayapura - Maikel Silak; Irja T. Simbiak; Tommi Tommi (Fakultas Teknik Universitas Cenderawasih, 2024)
Community-Based Sanitation Program (SANIMAS) is a form of government policy implemented by the Ministry of Public Works since 2006 regarding sanitation improvements and is designed to empower communities, Low Income, Communties (MBR), as well as disadvantaged communities, communities living in dense residential areas, slums, and poor in urban and rural areas. Apart from that, the SANIMAS program also places the community as actors, decision makers and those responsible for activities starting from identification, planning, implementation, management and supervision. This research aims to look at community perceptions of the implementation of the Sanimas Program, as well as look at the MCK infrastructure that has been built by the government to empower underprivileged communities and areas with high defecation rates. The method used in this research is the Qualitative Descriptive method. The results of this research show that the Sanimas Program ini Yoboi Village has been implemented by building 22 toilet units for 22 residents’ houses, whilw 40 other housing units have not been built, out of a total of 62 housing units there. The Sanimas Program is able to have a positive impact on people’s lives, namely increasing the level of dignity of the community, improving the level of environmental and community helath. Im implementing the Sanimas Program, the government has not fully built the infrastructure needed by the community to answer Sanitation problems. In terms of community empowerment, not all of them have been able to be empowered due to a lack of guidance from the regional government for the target community.